PEMBELAJARAN MATEMATIKA DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA 4-5 TAHUN - Ardiana, Reni; Ika Pratiwi, Yuni; Agustina Dwi H, Rinawati (SISTEMA: Jurnal Pendidikan, 2024)
This study aims to explore how mathematics learning contributes to the cognitive skill development of children aged 4-5 years. The subjects of this study are children aged 4-5 years. Using a qualitative approach, this research observes the teaching strategies employed and children's responses to learning. Data collection techniques were conducted through observations and interviews. The results show that play-based approaches, exploration, and interactive technology have a positive impact on children's critical thinking and problem-solving abilities. Keywords:Mathematics Learning, Cognitive, Early Childhood